Effect of aliskiren, a direct renin inhibitor, on the protective action of antiepileptic drugs against pentylenetetrazole‐induced clonic seizures in mice. (21st November 2018) - Łukawski, Krzysztof; Raszewski, Grzegorz; Czuczwar, Stanisław J.
Abstract: It has been demonstrated that certain angiotensin‐converting enzyme (ACE) inhibitors and angiotensin AT1 receptor antagonists can possess anticonvulsant activity. The purpose of the current study was to examine the effect of aliskiren, a direct renin inhibitor and a novel antihypertensive drug, against pentylenetetrazole (PTZ)‐induced clonic seizures in mice and on the protective activity of conventional antiepileptic drugs (AEDs) in this seizure model. Effects of aliskiren on the PTZ threshold and the protective efficacy of AEDs, such as clonazepam (CLO), phenobarbital (PB), valproate (VPA), and ethosuximide (ETX) in the PTZ test, were evaluated in adult Swiss mice. Aliskiren and AEDs were administered intraperitoneally (i.p.) while PTZ (50–100 mg/kg) was injected subcutaneously (s.c.). The rota‐rod and passive avoidance test were used to assess the adverse effects of the combined treatment with aliskiren and AEDs. Aliskiren, at the dose of 75 mg/kg, significantly raised the PTZ threshold ( P < 0.05). Furthermore, aliskiren, at the subthreshold dose of 50 mg/kg, significantly enhanced the protective action of CLO ( P < 0.01), PB ( P < 0.01), and VPA ( P < 0.05) but not ETX ( P > 0.05) in the s.c. PTZ test. Motor coordination in the rota‐rod test and long‐term memory in the passive avoidance task were not impaired by the combined treatment of the drugs. This study suggests that treatment with aliskiren can be useful in hypertensive patients with myoclonic seizures. Certainly, a clinical verification of using aliskiren in such patients would be necessary.